Shared Mandates, Moral Hazard, and Political (Mis)alignment in a Decentralized Economy - Antonio Estache; Grégoire Garsous; Ronaldo Serôa da Motta (Inter-American Development Bank (IDB), 2015)
This paper investigates the effects of political (mis)alignment on public service delivery when mandates are shared between state and local governments. We analyze sewage treatment policies in the state of S\~ao Paulo, Brazil. Relying on difference-in-differences estimations, we establish a causal relationship between political alignment and higher sewage treatment provision. Conceptually, we find that, with uncertain local commitment and weakly enforceable local obligations, shared mandates lead to a moral hazard issue implying service under-provision. Our results show that political alignment attenuates such moral hazard effects.
hdl:11319/6882
Keywords: H40; H54; H72; P48; 330; political alignment; infrastructure provision; water and sanitary services; moral hazard; Brazil